PENDIDIKAN SEKS DALAM ALQURAN DAN HADITS SERTA PERANAN ORANG TUA DALAM PENGENALAN SEKS TERHADAP ANAK - Yenti Murni; Rusydi, A. M; Charles; Nidaul Kher (Kampus Akademik Publiser, 2023)
Abstract. Different understandings of the meaning of sex education make people misinterpret the word sex education as something dirty and only teaches sexual relations between men and women. In fact, sex education is part of education as a whole, so the notion of sex education is closely related to education in general. Sex education in Islam is an integral part of the education of faith, morals, and worship. The detachment of sex education with these three elements will cause the direction of sex education to be unclear, it may even lead to misguidance and deviation from the original purpose of humans doing sexual activities in the context of devotion to God. Therefore, the implementation of sex education should not deviate from the demands of Islamic law and start from an early age so that there is no misunderstanding.